Pathways to Fatherhood: Psychological Well-Being Among Israeli Gay Fathers Through Surrogacy, Gay Fathers Through Previous Heterosexual Relationships, and Heterosexual Fathers - Shenkman, Geva; Siboni, Ofer; Tasker, Fiona; Costa, Pedro Alexandre (Frontiers in Psychology, 2020)
This study explored differences in psychological well-being as assessed by life satisfaction, parenthood satisfaction, depressive symptoms and the Big Five personality dimensions among 219 Israeli fathers; 76 gay men who had become fathers through a heterosexual relationship, 63 gay men who had become fathers through surrogacy, and 78 heterosexual men. After controlling for sociodemographic characteristics, gay fathers through surrogacy reported greater satisfaction with parenthood, greater satisfaction with their lives, and reported higher levels of extraversion when compared to heterosexual fathers. No significant differences emerged between the three groups on depressive symptoms, neuroticism, conscientiousness, agreeableness, and openness to experience. These ﬁndings emphasize the predominant similarities and some possible differences on psychological well-being between the different paths to fatherhood. This study is one of the first to compare several paths to fatherhood on psychological well-being, thus illuminating the contribution of fatherhood route to psychological well-being in an era where gay men are increasingly becoming fathers in diverse ways.